Pengaruh Bulk Density Dan Total Porosity Terhadap Pengelolaan Lahan Untuk Produksi Tanaman Pangan - Waruwu, Irwilan; Bu'ulolo, Sozanolo (CV. SINAR HOWUHOWU, 2024)
Proper land management is essential to increase food crop productivity. Two soil parameters that affect land management are bulk density and total porosity. Bulk density describes the density of the soil, while total porosity indicates the pore space in the soil that is filled with air and water. This study aims to analyze how bulk density and total porosity affect land management for food crop production. The methods used are direct measurements in the field and laboratory analysis of soil samples. The results showed that bulk density and total porosity have significant correlations with several other soil parameters that are important for plant growth, such as soil moisture, water infiltration, and soil porosity. The implication is that land management must consider the values ​​of bulk density and total porosity to optimize food crop productivity.